PENGARUH KOMITMEN ORGANISASI, PERILAKU KEPEMIMPINAN DAN ETIKA KERJA TERHADAP KINERJA PEGAWAI - Sahibuddin Sahibuddin; Samdin Samdin; Asrip Putera (Pascasarjana Universitas Halu Oleo, 2019)
The objective of this study is to examine and explain the effect of Organizational Commitment, Leadership Behavior and Work Ethics on Employees Performance at Wakatobi Regency Regional Secretariat. The approach of this study was survey with explanatory research design. Data is collected by using survey method with questionnaires and interviews. The population of this study is 59 people in Wakatobi Regency Regional Secretariat. Because the population of the study is relatively small, all the populations in the study were made as respondents. The analytical equipment used was Multiple Linear Regression Analysis.The result shows that Organizational Commitment, Leadership Behavior and Work Ethics has positive and significant effects on employees performance, and partially organizational commitment has positive and significant effects on employees performance; Leadership behavior has positive and significant effects on employee performance, and Work Ethics has positive and significant effects on employees performance.Keywords: organizational commitment, leadership behavior, work ethics, and employees performance